Prenatal depressive symptoms, infant temperament, parental role satisfaction, and child adjustment: a longitudinal serial mediation - Stürmlinger, Linda Luisa; Ray, Jana; Krause, Mischa von; Nonnenmacher, Nora; Alpers, Georg W.; Zietlow, Anna-Lena (Journal of family psychology, 2025)
Maternal prenatal depressive symptoms (PD symptoms) pose a risk factor for child adjustment difficulties (CAD), defined as internalizing and externalizing symptoms. This study examined the underlying mechanisms of the link between PD symptoms and CAD in a longitudinal study. Longitudinal data from pregnancy to age 3, encompassing four assessment points, were analyzed for N = 582 mothers participating in the German family panel pairfam. We tested a serial mediation model considering infant temperament during the first year and mothers’ parental role satisfaction 2-3 years postpartum as mediators between PD symptoms and CAD at age 3. PD symptoms significantly predicted CAD. We could not find that infant temperament or parental role satisfaction mediated between PD symptoms and CAD, though all variables were significantly associated on a correlational level. Furthermore, infant temperament partially mediated between PD symptoms and parental role satisfaction. Our findings emphasize the importance of the infant’s temperament in the scope of PD symptoms for the mother’s perception of her parental role, with possible adverse long-term effects for the mother-child relationship and the child. This study provides evidence for a complex bidirectionality between maternal and child-driven effects in the transmission of adverse effects of maternal PD symptoms. Depressive symptoms, even on subclinical levels, should already be targeted prenatally to prevent negative long-term effects for mothers and children. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 30.06.2025